2022
DOI: 10.3390/polym14163367
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polycarboxylate Viscosity Reducer and the Effect of Different Chain Lengths of Polyether on Viscosity Reduction of Heavy Oil

Abstract: Since there are not many studies on the application of polymeric surfactants in viscosity reduction emulsification of heavy oil, a series of polyether carboxylic acid–sulfonate polymeric surfactants were synthesized. The viscosity reduction performance and the effect of different chain lengths on the viscosity reduction effect were also investigated. The viscosity reduction, emulsification, wetting, and foaming performance tests showed that the viscosity reduction performance of this series of polymeric surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The dropwise addition time of acrylic acid and sodium p -styrenesulfonate was 2 h, and the dropwise addition time of potassium persulfate was 2.5 h. After the dropwise addition, the reaction was stirred and kept at 80 °C for another 5 h. After that, the product was cooled to room temperature, and the pH was adjusted to around 7-8 with a 20 wt% sodium hydroxide solution. The resulting solution was the polyether carboxylate viscosity reducer, APAS [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dropwise addition time of acrylic acid and sodium p -styrenesulfonate was 2 h, and the dropwise addition time of potassium persulfate was 2.5 h. After the dropwise addition, the reaction was stirred and kept at 80 °C for another 5 h. After that, the product was cooled to room temperature, and the pH was adjusted to around 7-8 with a 20 wt% sodium hydroxide solution. The resulting solution was the polyether carboxylate viscosity reducer, APAS [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…In our previous work [ 30 ], we synthesized polyether carboxylate viscosity reducers with different side chain lengths, performed viscosity reduction and emulsification performance tests, and achieved the optimal structures and reaction conditions. However, up to now, the effect on electrical properties of polyether carboxylate has been scarcely studied systematically, although electrical properties have a potential impact on viscosity reduction in heavy oil [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some emulsification viscosity reduction can even reduce the viscosity more than 99%. According to their chemical structure, emulsifiers are usually divided into cationic, anionic [ 13 , 14 , 15 ], nonionic, amphoteric, and nonionic—anionic complex. However, cationic viscosity reducers are easily adsorbed or precipitated by the formation, so they are rarely used as an oil displacement agent or emulsified viscosity reducer.…”
Section: Introductionmentioning
confidence: 99%
“…The viscosity reduction performance and the effect of different chain lengths on the viscosity reduction effect were also investigated. Viscosity reduction, emulsification, wetting, and foaming performance tests showed that the viscosity reduction performance of this series of polymeric surfactants was excellent, with a viscosity reduction rate exceeding 95% [ 13 ]. There are few studies on nonionic and amphoteric viscosity reducers.…”
Section: Introductionmentioning
confidence: 99%
“…However, biological methods usually have great limitations, such as temperature, salinity, etc., and the reproductive process of microflora is difficult to control . Emulsification is an efficient and widely used method for chemical viscosity reduction. Natural surfactants such as asphaltenes and resins in heavy oil facilitate the formation of stable and viscous water-in-oil (W/O) emulsions .…”
Section: Introductionmentioning
confidence: 99%